Childhood parasitic infections and gastrointestinal illness in indigenous communities at Lake Atitlán, Guatemala - Amber Roegner; Mónica N. Orozco; Claudia Jarquin; William Boegel; Clara Secaira; Marlin E. Caballeros; Lujain Al-Saleh; Eliška Rejmánková (PeerJ, 2021)
Lake Atitlán has experienced a decline in water quality resulting from cultural eutrophication. Indigenous Mayans who already face disproportionate health challenges rely directly on the lake water. Our objectives were to: (1) estimate prevalence of shedding of water-borne fecal parasites among children 5 years of age and younger, (2) assess household-reported incidence of gastrointestinal illness in children, and (3) characterize water sources, treatment, and sanitation conditions in households. We hypothesized that household use of untreated lake water results in increased risk of shedding of parasites and gastrointestinal symptoms. A cross-sectional fecal sampling and physical exam of 401 children were conducted along with WASH surveys in partnership with healthcare providers in seven communities. Fecal samples were screened for Giardia lamblia and Cryptosporidium parvum, using a rapid ELISA, with a portion examined by microscope. The prevalence of parasite shedding was 12.2% (9.7% for Giardia; 2.5% for Cryptosporidium). Risk factors for Giardia shedding included age 3 years or older (3.4 odds ratio, z-stat = 2.781 p = 0.0054), low height-for-age z-score (2.3 odds ratio, z-stat = 2.225, p = 0.0216), lack of any household water treatment (2.5 odds ratio, z-stat = 2.492, p < 0.0012), and open access to household latrine (2.04 odds ratio, z-stat = 1.992, p = 0.0464). The majority (77.3%) of households reported water treatment, boiling and gravity fed filters as the most widespread practices. The vast majority of households (92%) reported usage of a latrine, while 40% reported open and shared access beyond their household. An overwhelming majority of households reported diarrhea and fever several times per year or greater, with approximately half reporting vomiting at that frequency. Lake water use was identified as a risk factor for households reporting frequent gastrointestinal symptoms (odds ratio of 2.5, 4.4, and 2.6; z-stat of 3.10, 3.65, and 3.0; p-values of 0.0021, 0.0003, and 0.0028, for diarrhea, vomiting, and fever, respectively) in children 5 years of age and younger. The frequency of gastrointestinal illness with a strong link to lake drinking water cannot be explained by the prevalence of protozoa, and risk from other enteropathogens must be explored. Improving access to water treatment and sanitation practices could substantially reduce the parasite burden faced by developing children in the region.